Prevalence Of Chronic Suppurative Otitis Media In School-Aged Children And Associated Risk Factors. - Hasnain, Fahad; Ali, Farman; Hafeez, Muhammad; Samiullah, Samiullah; Shinwari, Wajih Ud Din; Ahmad, Siyyar (Journal of Neonatal Surgery, 2025)
Background:Chronic suppurative otitis media (CSOM) is a chronic middle-ear infection that is typified by repeated otorrhea via a perforation of the tympanic membrane and is a leading cause of preventable childhood hearing loss, negatively influencing speech development, academic achievement, and quality of life in low and middle-income countries. Purpose: To identify the commonness of CSOM among children of school-going age and to assess how it is connected to the chosen sociodemographic, environmental, and clinical risk factors. Methodology: It was a cross-sectional study whose participants were school-going children between 5 and 15 years of age who were chosen using multistage random sampling methods in both the public and the private schools in District Peshawar. Informed consent was obtained, and a structured questionnaire that included demographic profile, household crowding, parental education, passive smoking exposure, history of recurrent upper respiratory tract infections (URTI), and ear-hygiene practices was used to collect data. Otoscopic observation was done to detect perforation of the tympanic membrane, active or recent otorrhea, which is characteristic of CSOM. SPSS version 24.0 was used to analyze the data. Chi-square tests were used to test the associations, and multivariate logistic regression was used to identify independent predictors. Results: A total of 100 children were enrolled, including 56 males and 44 females, with a mean age of 9.8 ± 2.7 years. CSOM was diagnosed in 14 children, giving a prevalence of 14.0%. Unilateral disease was present in 71.4% and bilateral in 28.6% cases. CSOM was significantly associated with household crowding (p = 0.004), passive smoking exposure (p = 0.018), recurrent URTI (p < 0.001), and prior acute otitis media (p = 0.002). On multivariable analysis, recurrent URTI (adjusted OR = 4.9; 95% CI: 1.6–14.8) and household crowding (adjusted OR = 3.7; 95% CI: 1.2–11.3) remained independent predictors. Conclusion: CSOM is common in school-aged children, and it has a close association with risk factors that can be prevented. Screening and dedicated interventions of public health at the school level can significantly minimize chronic ear disease and its educational effects.